Toleransi Beragama Perspektif Al-Qur’an; Counter Terhadap Gerakan Transnasional di Indonesia - Iga Kurniawan (At-Ta'wil: Jurnal Pengkajian al-Qur'an dan at-Turats, 2020)
Indonesia is an archipelago that is rich in traditions, culture, ethnicity, religion and race. This wealth shows that Indonesia is a plural, developed country. However, the state's wealth which should be a valuable asset is tarnished by the interests of certain groups to dominate politically as well as power over other groups until it is manifested by various violence and sadistic actions, especially in the name of religion. Transnational movements that try to eliminate the values of tolerance and harmony between religious communities are partly based on a partial understanding of the Koran, so it is necessary for the author to re-examine tolerance in the perspective of the Koran as a counter to transnational movements.